An introduction to marriage and family therapy - Wetchler, Joseph L.; Hecker, Lorna L. (New York, NY : Routledge/Taylor & Francis Group, 2015)
'Now in its second edition, this text introduces readers to the rich history and practice of Marriage and Family Therapy, with 32 professionals from across the US presenting their knowledge in their areas of expertise. This blend of approaches and styles gives this text a unique voice and makes it a comprehensive resource for graduate students taking their first course in Marriage and Family Therapy. The book is divided into three sections: Part 1 focuses on the components on which 21st century family therapy is based and summarizes the most recent changes made to not only therapeutic interventions, but to the very concept of'family.' Part 2 presents an overview of the 7 major theoretical models of the field: structural, strategic, Milan, social constructionist, experiential, transgenerational, and cognitive-behavioral family therapy. Each chapter in this section - Focuses on the founder of the theory, its theoretical tenants, and its key techniques - Shows how the model focuses on diversity - Presents the research that supports the approach Part 3 addresses specific treatment areas that are common to marriage and family therapists, such as sex therapy, pre-marital therapy, research, and ethics and legal issues'--
Includes bibliographical references and index.
Keywords: Family psychotherapy; Marital psychotherapy